A Castle in the Air? The Building, Arms, Action and Incident on the Eleventh-Century 'Castle' Capital from Westminster Hall. (2nd July 2016) - Impey, Edward
Abstract : The restoration of Westminster Hall in the 1830s revealed a number of eleventh-century carved capitals, one depicting, as then described, 'an armed man assailing a castle'. Aided by archaeological evidence from Abinger (Surrey), the 'castle' can be convincingly interpreted as a motte-top tower, carried by earth-fast posts, open-sided below and faced above with boards painted to resemble masonry. It is the only known depiction in elevation of a type of tower that is likely, given its simplicity, to have been widely used in the eleventh and twelfth centuries. The assailant, armed with an axe, carrying a round shield and wearing a helmet with nasal, is shown climbing the tower's external stair at the moment of being despatched or wounded by the defender's spear. The incident, an individual action rather than a 'siege' as such, has many oddities, and may represent a topical event or scene from history or mythology. The story of the Trojan War is suggested as a possible source.